CBMs in South Asia : potential and possibilities - Banerjee, Dipankar; Regional Centre for Strategic Studies (Colombo, Sri Lanka) (Colombo : Regional Centre for Strategic Studies, 2000)
Contributed articles.
Keywords: Confidence and security building measures (International relations) -- South Asia